Implications of Visuospatial Skills and Executive Functions for Learning Mathematics - Helyn Kim; Claire E. Cameron (SAGE Publishing, 2016)
The purpose of this article is to review the literature and apply a developmental neuroscience perspective in investigating the role of two interrelated cognitive processes-executive functions (EFs) and visuospatial (VS) skills-which have been empirically and theoretically linked to children's mathematics achievement. To illustrate, we provide evidence of the importance of EFs and VS skills for mathematics learning by examining and comparing the distinct cognitive profiles of individuals with autism spectrum disorder and Williams syndrome. By simultaneously considering two cognitive processes that are implicated in mathematics, we offer insight into the underlying mechanisms by which EFs and VS skills support children's learning and acquisition of mathematical skills, as well as how neuroscience research may successfully inform educational practice.